Preoperative planning by osteotomy master software helps to improve the accuracy of target limb alignment in high tibial osteotomy - Axiang He (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background The accuracy of targeted lower limb alignment correction following HTO is closely related to patients’ pain relief and knee joint survival time. How to accurately perform osteotomy and how to obtain the ideal target limb alignment to maximize the curative effect are the difficulty in HTO practice. The purpose of this study is to evaluate the predictive and application value of osteotomy master software (OsteoMaster) in coronal plane preoperative planning of high tibial osteotomy. Method Sixty-seven patients with medial compartment osteoarthritis and varus deformity treated by medial open-weight high tibial osteotomy were enrolled and divided into observation group (31 cases) and control group (36 cases). The observation group was planned by OsteoMaster, while the control group was planned by Miniaci. The preoperative predicted values of osteotomy depth, open height, correction angle, WBL ratio, and FTA of the observation group were compared with the actual intraoperative values to study their accuracy. The operative time, blood loss, number of fluoroscopy, and WBL ratio were compared between the observation group and the control group to study its application value. Result There was no significant difference between two groups in preoperative prediction and intraoperative reality of osteotomy depth, open height, correction angle, FTA, and WBL ratio (P > 0.05). The operation time and number of fluoroscopy in the observation group were significantly less than those in the control group (P < 0.05), while the difference in blood loss was not statistically significant (P > 0.05). The good rate of WBL ratio was 87.1% in the observation group and 75% in the control group. Conclusion OsteoMaster has predictive value in osteotomy depth, open height, correction angle, FTA, and WBL ratio of HTO, which is also helpful to reduce the number of fluoroscopy, shorten the operation time, and improve the accuracy of target limb alignment. The drawback of this approach is 2-dimensional approach in contrast to 3-dimensional preoperative planning that is including the more real study.